Stable isotope probing of amino sugars – a promising tool to assess microbial interactions in soils†. (17th May 2013) - Bodé, Samuel; Fancy, Rubeca; Boeckx, Pascal
Abstract : RATIONALE: Bacteria and fungi are key protagonists of litter degradation in soils. Often they have to share common substrates, which has led to special interactions between both microbial groups. Due to the historical classification of bacteriology and mycology as two separate fields of microbial research, the understanding of their interactions in soils is scares, while it is crucial for a better understanding of nutrient recycling and carbon sequestration in soils. Therefore, a new approach to investigate fungal‐bacterial interactions is proposed using stable isotope probing of their amino sugar biomarkers. METHODS: An agricultural soil, under different microbial inhibition treatments, was incubated for 21 days with 13 C‐labeled plant residues. Residue respiration was determined by measuring the isotopic composition and concentration of the produced CO2, using an isotope ratio mass spectrometer coupled to a trace gas preparation unit. At several time points, amino sugars were extracted, after hydrolysis, from the incubated microcosms. Subsequently, 13 C‐isotopic composition and concentration of the individual amino sugars was determined using liquid chromatography/isotope ratio mass spectrometry. RESULTS: When the bacterial community was inhibited, fungi showed an increased capacity to metabolize added plant residues indicating an antagonistic effect of bacteria towards fungi. Furthermore, the fungal community was able to take benefit of a larger portion of the residue, which indicates that this antagonism was at least partially due to interference competition. On the other hand, the inhibition of the fungal community appeared to have a very negative effect on the capacity of bacteria to metabolize added plant residues. Therefore, the bacterial community could be considered as playing a parasitic type role towards fungi during litter degradation. CONCLUSIONS: This newly developed methodology proved to be very useful for elucidating microbial interactions during plant residue degradation. Copyright © 2013 John Wiley & Sons, Ltd.